TRANSFORMASI PENDIDIKAN PESANTREN ERA MODERN : INTEGRASI NILAI KEISLAMAN TEKNOLOGI DAN KOMPETENSI ABAD 21 - Nurul Ulfa Ramadhani; Sarah Fadilah Azzahra; Gunawan; Zuhairansyah Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The transformation of Islamic boarding school (pesantren) education has become a necessity in responding to the rapid development of science, technology, and the demands of 21st-century competencies. However, this transformation must remain grounded in Islamic values, which constitute the fundamental identity of pesantren. This study aims to analyze the transformation of pesantren education in the modern era through the integration of Islamic values, the utilization of technology, and the strengthening of 21st-century competencies. The study employs a qualitative approach using a library research method. Data were collected from various sources, including books, journal articles, research reports, and other relevant scientific documents. Data analysis was conducted through content analysis involving data reduction, data presentation, and conclusion drawing. The findings reveal that the transformation of pesantren education is manifested through three major aspects: (1) the integration of Islamic values as the educational foundation for developing students' character and morality; (2) the utilization of technology to enhance learning quality, information accessibility, and institutional management; and (3) the strengthening of 21st-century competencies, including critical thinking, creativity, communication, collaboration, and digital literacy. These three aspects are integrated into an educational model that enables pesantren to adapt to contemporary developments while preserving its Islamic identity. Therefore, pesantren play a strategic role in producing Muslim generations who are morally grounded, competent, and capable of competing in the global era.